The Influence of Education, Community Income Level and Investment Motives on the Demand for Sharia Insurance in Sambirejo Timur Village, Percut Sei Tuan District, Deli Serdang Regency - Nita, Nita Erdina; Imsar; Nasution, Juliana (ProBisnis : Jurnal Manajemen, 2024)
This study aims to determine the influence of education, community income level and investment motives on the demand for sharia insurance. This study uses a quantitative approach and uses primary data through distributing questionnaires to the people of Sambirejo Timur Village. The sample in this study was 100 respondents. The data was processed through the SPSS version 26 for windows program with. The results of this study indicate that the t-test or partial education has a significant effect on the demand for sharia insurance. Income level does not affect the demand for sharia insurance and investment motives have a significant effect on the demand for insurance and there is an influence of education, income level and investment motives on the demand for sharia insurance. The coefficient of determination (R2) is 0.645. These results indicate that the variables of education, income level and investment motives that can be explained by the variable of demand for sharia insurance are 64.5% while the remaining 35.5% is explained by other variables that are not included in the regression model